Diplomasi Politik Belanda terhadap Kerajaan Banggai dalam Naskah Perjanjian 113 8/21 - Siti Aliyah; Dewaki Kramadibrata (Manuskripta, 2021)
This article discusses the manuscript 113 8/21 in the collection of the National Library of Indonesia. This manuscript is a letter of agreement between the Kingdom of Banggai, the Dutch East Indies Government, and Ternate which was made in 1828 AD. Treaty Manuscript 113 8/21 contains 13 articles that regulate all aspects of the life of the Kingdom of Banggai. This study was researched using the literature study method and historical approach. This research was conducted to analyze the forms of political power and diplomacy used by the Dutch East Indies and Ternate Governments toward the life of the Banggai people in the Treaty Manuscript 113 8/21. Based on the analysis, there are three aspects that are controlled by the Dutch East Indies and Ternate Governments: political, legal, and economic aspects. To be able to do this, the Dutch East Indies Government launched a strategy of Coercive Diplomacy and Market Diplomacy.---Penelitian ini membahas naskah dengan kode 113 8/21 koleksi Perpustakaan Nasional Republik Indonesia. Naskah ini merupakan surat perjanjian antara Kerajaan Banggai, Pemerintah Belanda, dan Ternate yang dibuat pada tahun 1828 M. Naskah 113 8/21 berisi 13 pasal yang mengatur segala aspek kehidupan Kerajaan Banggai. Dengan menggunakan metode studi pustaka dan pendekatan sejarah, penelitian ini dilakukan untuk menganalisis bentuk kekuasaan dan diplomasi politik yang digunakan Pemerintah Belanda dan Ternate terhadap kehidupan masyarakat Banggai dalam Naskah Perjanjian 113 8/21. Berdasarkan analisis yang dilakukan terhadap naskah perjanjian 113 8/21, terdapat tiga aspek yang dikuasai Belanda dan Ternate terhadap Kerajaan Benggai, yaitu aspek politik, hukum, dan ekonomi. Untuk dapat melakukan hal tersebut, Pemerintah Belanda melancarkan strategi Coercive Diplomacy dan Market Diplomacy.